Streamlining Content Marketing: Antecedents of Productivity in the Age of AI Expansion - Basalamah, Muhammad Syafii A.; Regina, Regina; Laekkeng, Mursalim; Hasan, Said (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
The expansion of AI directly affects productivity levels, particularly for content creators, as it alters many aspects of work. This study investigates the impact of AI utilization and content quality on marketing team productivity. A purposive sampling technique employed in this quantitative research distributed an online questionnaire to 200 respondents (content marketing creators). The data is analyzed using structural equation modelling (SEM) with SMART-PLS 4. AI improves content quality and marketing team productivity, whereas content quality boosts productivity. However, AI directly affects team performance. AI is essential for content marketing quality and efficiency. The data used in this study were exclusively derived from questionnaires, which may be subject to limitations due to the subjectivity of respondents or bias in their responses. However, this study can be a foundation for companies and content creators to improve audience personalization and enhance productivity through AI.